Análise comparativa da matriz curricular dos cursos de graduação em agronegócio nas instituições superiores da região centro-oeste - Luís Capaz, Mário (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This study aims to identify the structural determinants in the curriculum of undergraduate courses in agribusiness in the Midwest region. Identify multidisciplinary, disciplinary focus, humanistic education and academic freedom. Comparing public and private, technologist and a BA, classroom teaching and distance. The research is exploratory, descriptive literature, documentary and comparative. Data were collected through desk research – electronic – the portal of the MEC and the websites of each university or college. The survey results allow us to conclude that the Undergraduate courses Agribusiness in the surveyed universities have a higher percentage of class hours in the discipline of management, then the economy. It was observed that some are multidisciplinary courses. The humanistic education have become a lower percentage and the non-existent academic freedom.